Zmiany roślinności na siedlisku olsu jesionowego w lasach północno-wschodniej Polski - Czerepko, Janusz (Leśne Prace Badawcze, 2010)
The habitat of ash-alder swamp forest, was studied in a phytosociological context. A census of changes in the species composition of natural communities was performed 40 years after the original survey had been carried out in 31 relevés located in natural forests. The study sites were localized in Augustów and Białowieża nature reserves. Re-sampling of relevés followed the same Braun-Blanquet assumptions as previously. The chemical characteristics from nine soil cores were also analysed, and the peat thickness and ground water table level were measured close to every vegetation sample. Phytosociological surveys were conducted in both spring and summer. Comparative analysis of vegetation data from the two periods (old – new relevés) was performed for selected variables: species richness, layers cover, ecological indicator values, number of occurrences and cover coefficients of species and syntaxonomical groups. The analysis of changes in the natural communities of vegetation occurring on ash-alder swamp forest habitat over the last 40 years indicated that decreasing humidity has caused the succession of ash-alder swamp forest to moist variants of oak-lime-hornbeam forest. An increase in cover of the understorey layer (and parallel decrease in cover of the moss layer) was evident in every sample. The species richness increased significantly over time, but this was mainly caused by the increasing number of species in the herbal flora. The species richness increasing significantly, but it was mainly caused by increasing of species number in herbal flora.